Perplexing presentations in paediatric gastroenterology. Issue 11 (November 2018) - Pigott, Anna Jane; Saran, Shashwat; Monaghan, Sean
Abstract: The nature of gastroenterological conditions often lead the clinician to rely on the history offered by the parents or carers to make a diagnosis and create a management plan. It is no coincidence that some of the most frequent presentations of fabricated or induced illness (FII) are with apparent gastroenterological complaints. This review details elements in the presenting history of vomiting, constipation, diarrhoea, blood in stool, faltering growth and abdominal pain that potentially make FII a more likely diagnosis, and proposes a management approach to a suspected presentation of FII.